ANALISIS PERBANDINGAN PERFORMA GALOIS COUNTER MODE (GCM) PADA AES DAN CAMELLIA UNTUK ENKRIPSI DAN DEKRIPSI DATA - Usman Hidayatulloh Sidiq; Akhmad Zaini; Danang Aditya Nugraha (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2026)
Digital data security has become a critical necessity in tandem with the increasing threats to information confidentiality and integrity in the modern era. The Advanced Encryption Standard (AES) and Camellia are to internationally standardized block cipher algorithms with equivalent security levels but distinct internal structures. The Substitution-Permutation Network (SPN) in AES and the Feistel Network in Camellia result in different performance characteristics. The lack of comprehensive research comparing both algorithms in Galois Counter Mode (GCM) using multithreading and hardware acceleration parameters serves as the background for this study. This research aims to compare the performance of AES and Camellia in GCM based on parameters including key size, file size, mode of operation, multithreading, and hardware acceleration. The implementation was conducted using the Java programming language and the BouncyCastle library. The result indicate that AES is superior, exhibiting a 30% higher processing rate. Multithreading efficiency is optimal at 2 threads but decreases at 8 threads due to thread management overhead. Hardware acceleration yields varied impacts, such as accelerating encryption time and slowing down the decryption time for AES. Overall, AES demonstrates superior performance, whereas Camellia remains competitive under specific conditions.